THE STUDY OF THE PRACTICE OF CLIL ON THE EXAMPLE OF THE GEORGIAN-AMERICAN SCHOOL PROGRESS - Nino Ioramashvili, (International Journal of Innovative Technologies in Social Science, 2024)
The research reveals the practice of teaching disciplines with the English language integrated learning on the example of the Georgian-American School Progress. Globalization and socio-economic factors impact the learning of languages according to their development. Due to the perspectives of the language policy, it promotes a different approach to language selection and its study. This often befits the adaptation of the methodology of the subject content and extends the linguistic competence based on the contents of the specific subjects. There are educational institutions in our society, where the English language is learned as a foreign language(EFL), in parallel with that, there are private institutions, where the content and English language integrated learning is implemented(CLIL).It is necessary to distinguish programs designed for ethnic minorities to learn the state language and integrate them into society, and foreign language programs. These namely English language programs help to master the content of subjects along with the English language.